Caminhos possíveis: Educação Ambiental para construção significativa de aprendizagens de estudantes com autismo nos cursos técnicos do Instituto Federal Da Bahia – Campus Brumado - Rocha , Kátia Quele Ferreira da Silva (2025)
People diagnosed with Autism Spectrum Disorder (ASD) face many challenges, two of which are the most common: communication and social interaction, which, due to their absence, are sources of restrictions from the point of view of social competence. So, how can we offer meaningful knowledge to individuals with ASD? How can these people demonstrate their learning? Given the particularity of each person and the behavioral differences they present, there is a need to search for new intervention methods that enable a more meaningful learning process and foster the individual autonomy of students with ASD. There is interest in researching a new methodology that presents pedagogical practices that significantly include people identified with the ASD diagnosis. Taking environmental education content as a theoretical basis, the main objective is to understand which pedagogical actions and differentiated methodological proposals can help productively include autistic students in school procedures, in order to highlight which factors help these students advance in theoretical and practical knowledge, based on their own environment and in an autonomous construction so that the interactive possibilities of these students are specified in the daily development of curricular activities in the school context. The theoretical framework was produced from the perspective of the legal frameworks of inclusion policies (BRASIL/MEC) and scholars who defend autonomous learning such as Freire (1996) and Brandão (1981), as well as discussions on inclusion with Mantoan (2020), deepening the discourses of multiple forms of learning, without being limited to a single education model, standardized in closed classrooms, but also in the free exploration of the new, without stereotypes, presenting the liberation that knowledge brings to the lives of those who are socially neglected by the absence of inclusion that urgently needs to be made real.